2021
DOI: 10.3390/ijms22020561
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Pathogenetic Role of Inflammasomes in Philadelphia Negative Chronic Myeloproliferative Neoplasms: A Narrative Review

Abstract: The last decade has been very important for the quantity of preclinical information obtained regarding chronic myeloproliferative neoplasms (MPNs) and the following will be dedicated to the translational implications of the new biological acquisitions. The overcoming of the mechanistic model of clonal evolution and the entry of chronic inflammation and dysimmunity into the new model are the elements on which to base a part of future therapeutic strategies. The innate immune system plays a major role in this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 111 publications
1
23
0
Order By: Relevance
“…Moreover, elevated levels of the inflammatory biomarker C-reactive protein in peripheral blood were associated with the PV phenotype (vs. essential thrombocythemia), older age, cardiovascular risk factors and a JAK2V617F allele burden over 50% [59,166], further supporting suggestions of a possible link between inflammation and atherosclerosis [58][59][60]. A seminal study from 2017 identified an association between mutations in the DTA and JAK2 genes and coronary disease [119].…”
Section: Thrombosismentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, elevated levels of the inflammatory biomarker C-reactive protein in peripheral blood were associated with the PV phenotype (vs. essential thrombocythemia), older age, cardiovascular risk factors and a JAK2V617F allele burden over 50% [59,166], further supporting suggestions of a possible link between inflammation and atherosclerosis [58][59][60]. A seminal study from 2017 identified an association between mutations in the DTA and JAK2 genes and coronary disease [119].…”
Section: Thrombosismentioning
confidence: 86%
“…Whether immune dysregulation can be considered an MPN disease “driver” or not remains to be fully elucidated [ 57 ], but the connection between chronic inflammation and vascular function, and atherosclerosis in particular, is indisputable [ 58 , 59 ]. For a comprehensive recent review on the role of inflammation in MPN, we refer readers to the article by Di Battista and colleagues published in this special edition [ 60 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Myeloproliferative neoplasms (MPNs) are rare, clonal disorders of the hematopoietic stem cell in which an uncontrolled proliferation of terminally differentiated myeloid cells is noted. Polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF) are included in the category of Philadelphia-negative, so-called classical MPNs, as opposed to chronic myeloid leukemia in which the Philadelphia chromosome, i.e., a shorter chromosome 22 resulting from a reciprocal translocation between the long arms of chromosomes 9 and 22, respectively, can be identified [ 1 , 2 , 3 ]. MPNs are known to exhibit phenotypic mimicry, can transform into secondary myelofibrosis or evolve to acute leukemia, and are marked by thrombotic complications which can often be the cause of death in these hematological disorders [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes are multiprotein complexes located in the cytosol. The main role of inflammasomes (as the part of the innate immune system) is to protect against invading pathogens but they are also implicated in the adaptive immune response via stimulation of the macrophages and regulation of Th17 cell differentiation [76]. More recently, they have been described in the cytokine storm in COVID-19 [77].…”
Section: Is Et Induced By Chronic Inflammation?mentioning
confidence: 99%